Identificazione e riconoscimento: una ricerca etnografica tra i membri del Collettivo Autonomo Viola - Katia Cigliuti (SHARE Press, 2018)
The paper aims at providing a reflection dealing with the "Collettivo Autonomo Viola", a leading organized group of supporters of the Fiorentina football club until a few years ago. Its organization, the in-group and out-group dynamics have been investigated through an ethnographic study. The manifold forms of identification of the Collettivo's members have allowed to think about the group membership as a primary form of self and other-recognition. Finally, some methodological issues dealing with the research experience are addressed, with a special emphasis on the relation between a researcher and an "ultras" group.